The survival of the German FinTech market: An accounting-based valuation - Leonard Stuckenborg; Jens Leker (The Journal of Entrepreneurial Finance (JEF), 2019)
The purpose of this paper is to examine the essential characteristics of the financial statements of FinTech start-ups and to investigate which figures of balance sheets are suitable indicators of failure for this still rising group of start-ups. We conduct a quantitative analysis of 595 annual reports of FinTech start-ups issued between 2007 and 2016. Our study reveals that the balance sheets have a high share of current assets and often show losses not covered by equity. Based on the financial variables, the period of three to five years after foundation could be identified as critical phase for the future survival of FinTech start-ups. Two years before failure significant changes in some balance sheet figures are recognizable. Using a logistic regression model, we identify accounting figures serving as indicators for the separation of the two groups, active and failed FinTech start-ups.
Keywords: C55; G21; G33; M13; M41; 650; FinTech; Accounting-based valuation; Business failure; Balance sheet analysis; Start-ups